Effectiveness of the Use of Ilocusion for Female Teachers in Class Management Processes in Smk Negeri 2 Jember - Selamet Supriyadi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2022)
The goals for the research to get a real picture of the realization and effectiveness of the use of illocution in the implementation of learning processes at SMK Negeri 2 Jember by female teachers as an effort to manage class X in the automotive and engineering department in the 2019/2020 school year. In this study researchers used qualitative descriptive methods. The data source used was a female teacher who took lessons in the automotive and engineering department. The choice of observation, record and note technique is chosen as a method of collecting research data. The results of the study illustrate the use of illocution in searle’s theory which consists of assertive, directive, commissive, expressive, and declarative in the effective implementation of classroom management processes.